Emissão quase branca de um complexo binuclear de disprósio(III) contendo dicarboxilatos - Lahoud, Marcelo G. [UNESP]; Davolos, Marian R. [UNESP]; De Jesus, Caio A.S. [UNESP]; Frem, Regina C. G. [UNESP] (My University, 2013)
This work reports the synthesis and characterization of the novel [Dy2(dcpz)2(suc)(H2O)8](H2O)1.5 (dcpz = 3,5-dicarboxypyrazolate, suc = succinate). The structure should probably consist of a binuclear species in which Dy3+ ions are linked by two different bridging organic ligands. Luminescent studies were carried out and revealed that the Dy3+complex exhibits a near white emission under UV excitation.
Near white emission of a binuclear complex of dysprosium(III) containing dicarboxylates